Early Works of A.M. Gorky: Translations, Publications, Interpretations - Tamara V. Kudryavtseva (Studia Litterarum)
Within the framework of comparative, contextual, and receptive analysis, this article examines the specificity of the early Gorky’s German reception (1900–1910). The article is an attempt to explain Gorky’s rapid entry into the Germanophone cultural space taking into consideration the problematics of Gorky’s early work and its specific implementation on the one hand and the specificity of the literary process in Germany in these years on the other. The article also takes into account editorial policies and practices as well as the overall political and literary orientation of the press and publishers. Some examples show the impact of Gorky’s work on the literary practice of German writers (R. Huch, G. Hauptmann, F. Wolf, etc.). The article reveals typical patterns of reception when German writers, translators, literary critics and, researchers of that time turn to Gorky’s work.